"An oedipal conflict on an epileptic basis": the diagnosing and treatment of behavioural problems in a Dutch child psychiatric clinic (1952–1962). (3rd May 2020) - Bakker, Nelleke; Smit, Milou
ABSTRACT: This article discusses the diagnosing and treatment of behavioural problems in a pioneering Dutch child psychiatric clinic in the 1950s. This was headed by Theo Hart de Ruyter, the first Dutch professor of child psychiatry and a psychoanalyst. It is generally assumed that during postwar years child psychiatry was primarily influenced by Freudianism with its focus on a nurture-related aetiology of children's behavioural problems. This assumption has, however, not been tested for the clinical practice. Did nature-bound explanations – referring to a child's neurological constitution, hereditary predisposition or brain dysfunction – disappear from the consulting room and was treatment with psychotropic drugs anathema to Freudians, in the way it has been suggested? We compare Hart de Ruyter's theoretical work with the contemporary expert discourse and with the way he and his team diagnosed and treated children, using clinical records. It turns out that both theory and practice and both aetiology and treatment mixed up nature and nurture. The use of an electro-encephalogram to rule out organic causes and of medication to speed up improvement of a child's behaviour does, however, not undo the predominant adherence of the clinic's staff to updated versions of Freudianism. It also demonstrates the semi-improvisational nature of early academic child psychiatry.